ANALISIS PEMANFAATAN SUMBER DAYA ALAM DANAU RAWA PENING KABUPATEN SEMARANG (Geo-Image, 2016)
The aim of this study is 1) to findpeople who utilize existing resources in Rawa Pening, 2) to determine the influence of the dominant vegetation of the population economic activity carried out in the Rawa Pening. The population in this study are the people who perform economic activities in Rawa Pening, totaling 392 people on two sites. The sampling technical used in this study is a stratified random sample. Research conducted taking 40 respondents. Data collection methods include: observation, questionnaire, and documentation. The data collected were analysis by using descriptive and simple linear regression analysis. Based on the results of the study, the population of economic activity related to the presence of Rawa Pening, fishermen, search hyacinth, peat miners, farmers, traders, boat services, as well as parking services. Resources are used in the form of fish, water hyacinth, and peat.